Enhancing Hajj pilgrimage experience and crowd management through Hajj-related keywords-based chipless RFID tags - H. Rmili; J. Yousaf; O. Boularess; M. Noman; B. Hakim; M. Aseeri; M. Bensaleh; F.A. Tahir (Alexandria Engineering Journal)
This study presents a novel application for deploying chipless RFID tags encoded with famous Hajj pilgrimage words. Inconspicuous, cost-effective, durable, and lightweight chipless RFID tags encoded with famous Hajj keywords of “Al-Ṣafa”, “Al-Marwa”, ''Al-Tawaf, “Bidayat Al Sai”, and “Bidayat Al Tawaf” are designed and fabricated. Each keyword is etched using cooper material on the flexible Kapton substrate of 66 mm× 66 mm x 0.1 mm size. The resonance characteristics of each realized tag are analyzed by observing the frequency shift in their backscattered radar cross section (RCS) in the range of 1–10 GHz using CST software. The RCS of each tag provides a unique electromagnetic coding signature to it, owing to their different current distributions. Thus, provides easy, cheap, and durable deployments of such tags for handling and managing large crowds’ movements such as during Hajj. The fabricated tags RCS results have very good agreement with simulation results. The integration of proposed chipless RFID technology with Hajj-related keywords can improve pilgrimage experiences with enhanced crowd management using an integrated wayfinding system based on the Internet of Things (IoT) as well as the preservation of historical and cultural heritage.